2009
DOI: 10.1002/mds.22541
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic networks for assessment of therapy and diagnosis in Parkinson's disease

Abstract: Neuroimaging and modern computational techniques like spatial covariance analysis have contributed greatly to the understanding of neural system abnormalities in neurodegenerative disorders such as Parkinson’s disease (PD). The application of network analysis to metabolic PET data obtained from patients with PD has led to the identification and validation of two distinct spatial covariance patterns associated with the motor and cognitive manifestations of the disease. Quantifying the activity of these patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Use of these analyses applied to positron emission tomography (PET) and SPECT images is not without precedent in Lewy body disease (Eckert et al ., 2007b): in Parkinson's disease (PD), SCAs have helped characterize the relationship between disease-specific covariant metabolic networks and cognitive and motor dysfunction as well as providing a biometric probe for therapeutic response, for example, to a dopaminergic medication (Eckert et al ., 2007a; Hirano et al ., 2009). In addition, more recently we have shown that a multivariate approach can usefully discriminate between DLB and AD with high sensitivity and specificity (Colloby et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Use of these analyses applied to positron emission tomography (PET) and SPECT images is not without precedent in Lewy body disease (Eckert et al ., 2007b): in Parkinson's disease (PD), SCAs have helped characterize the relationship between disease-specific covariant metabolic networks and cognitive and motor dysfunction as well as providing a biometric probe for therapeutic response, for example, to a dopaminergic medication (Eckert et al ., 2007a; Hirano et al ., 2009). In addition, more recently we have shown that a multivariate approach can usefully discriminate between DLB and AD with high sensitivity and specificity (Colloby et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Eidelberg et al identified a motor network in which higher metabolic activity in the lentiform nucleus and thalamus was associated with lower activity in the lateral frontal, paracentral, inferior parietal, and parieto-occipital areas and increased metabolism in the lentiform nucleus and thalamus (Eidelberg et al, 1994). Decreased expression of this network was associated with motor symptom improvement across interventions including pharmacotherapy (levo-dopa) and deep brain stimulation (Hirano et al, 2009). Greater brain activation in a motor sequence learning task in the left DLPFC, pre-supplementary motor area, and bilaterally in the superior parietal cortex was observed in the presence of a normal level of performance, which may suggest that increased activation of cortico-cortical pathways can compensate for striatal-cortical dysfunction (Fukuda et al, 2001).…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…By applying spatial covariance analysis, a network mapping approach based on principal components analysis, Eidelberg and colleagues have demonstrated characteristic alterations in functional brain organization in movement disorders 55, 56. The motor manifestations of PD are associated with the expression of a resting‐state metabolic network comprising increased regional activity in the globus pallidus, ventral thalamus, pons, and cerebellum, with relative reductions in parietal and premotor cortical activity (Fig.…”
Section: Parkinson's Diseasementioning
confidence: 99%